Degradation of Cibacron Red Dye using ZnO as a Catalyst Coated on the Surface of the Glass in the Photocatalytic Process - A. Sumartono; W. Andayani (Atom Indonesia, 2011)
Industrial discharges are the main causes of surface and groundwater contamination. Photocatalytic process is one of the methods that could be used to degrade organic compounds that released from industrial wastewater. Photocatalytic process of 10 ppm cibacron red dye with irradiation of UV lamp and ZnO as a catalyst that coated on the surface of the glass the size of 8 cm x 8 cm x 0.4 cm have been studied. Experiments consisting of (i) variation of ZnO catalyst at temperature 200oC, 300oC, 400oC, and 500oC, and (ii) the efficiency achieved by the resulting ZnO obtained from the best variation in (i) as the UV-photocatalytic agent in degradation of cibacron red dye. The UV irradiation was done at interval time 0; 0.5; 1; 2; ; 4; and 6 hours. Degradation could be achieved using ZnO catalyst at temperature 500oC, the percentage degradation at 289 nm, 515 nm, and 545 nm were 84.5±1.0%, 100% and 100%, respectively.Received: 20 November 2010; Revised: 27 October 2011; Accepted: 04 November 2011